Perception of Malaysian working adults on tax exemption for purchasing insurance for parents with pre-existing illness - Hindun Shahirah Zulkifli; Amuthaganesh Mathialagan; Nathan Vytialingam; Shasvine Viknesh; Dhashmini Thangavelu (Asian Journal of Social Science Research, 2023)
Some things in life are not worth risking, for instance our health and financial wellbeing. However, nearly half of the Malaysian population relies solely on government-supplied healthcare coverage and out-of-pocket expenses. They have no additional personal health insurance for their personal healthcare needs. The rise in the cost of healthcare has had an impact on access to care, especially for those with pre-existing conditions. This study aims to determine the acceptance and overall perception of working adults towards a tax exemption incentive for purchasing insurance that covers pre-existing medical illness expenses for their elderly parents. The findings would benefit senior citizens with pre-existing illnesses and catalyse insurance companies to develop health coverage for vulnerable populations. Additionally, the suggestions or recommendations may be useful for the government in putting forward policies that are advantageous for the healthcare system in Malaysia. This study utilises a cross-sectional design with descriptive statistic research methods, specifically survey instrumentation in a questionnaire form to collect data using a convenience sampling method. The survey form was given out and collected online through e-mail and Qualtrics, an online survey tool. Overall, 345 working adults in Malaysia participated in this study. The findings of this study show that working adults in Malaysia are likely to purchase health coverage for parents, have a positive attitude towards tax exemption for purchasing health coverage for parents and have a good intention to support tax incentives in purchasing health insurance for parents.